Self-Damping Mechanism in Blood Coagulation - Nemerson, Y; Silverberg, S.A; Jesty, J (Thrombosis and Haemostasis, 1974)
Two reactions of the extrinsic pathway of coagulation, the activations of Factor X and prothrombin, have been studied in purified systems and shown to be self-damping. Factor X was activated by the tissue factor - Factor VII complex, and prothrombin by two systems: the coagulant protein of Taipan venom, and the physiological complex of activated Factor X, Factor V, lipid, and calcium ions. In each case the yield of enzyme, activated Factor X or thrombin, is a function of the concentration of activator. These and other observations are considered as a basis for a control mechanism in coagulation.